The Transformation of Women's Characters in the Novel of Midah Si Manis Bergigi Emas by Pramoedya Ananta Toer (Study of Feminism) - Andry Sulastri (Budapest International Research and Critics University, 2022)
The novel Midah Si Manis Bergigi Emas by Pramoedya Ananta Toer describes the story of a woman named Midah Si Manis Bergigi Emas who is so tough that she can survive and fight the vicious life that women face. Women's existence in this novel consists of women who work as singers, never give up, have a strong personality, independent, and can see the otherness as a child, mother, and singer's wife. Meanwhile, gender inequality comes in the form of sexual violence, physical violence, postal violence, marginalization in the form of layoffs, marginalization in the form of discrimination in the household, subordination in the household, negative stereotypes of women, and multiple workloads. Gender inequality is a type of discrimination between men and women. Gender inequality takes place when women are subjected to violence, are unable to make decisions, and so on.